The Anti-Bacterial Effect of Eucalyptus and Medlar Extracts Against Klebsiella Pneumonia in Rasht Hospitals - Maryam Basboos; Leila Asadpour; Houra Pourghafar (Fasa University of Medical Sciences, 2020)
Background & Objective: Klebsiella pneumonia is an opportunistic pathogen in nosocomial infections. Nowadays using plant-based drugs against drug resistant bacterial infections is gaining special importance. The aim of this study was to evaluate the prevalence of extended spectrum beta lactamase producing clinical isolates of Klebsiella pnemoniae and the antibacterial effects of aquatic and ethanol extracts of Eucalyptus and Medlar against these bacteria in Rasht. Materials & Methods: In this study, a total of 45 isolates of K. Pneumonia were collected from urinary tract infections. ESBL production was determined by the double disk diffusion and disk diffusion was tested and specific primers PCR method was used to detect TEM and SHV genes. To investigate inhibitory effect of Eucalyptus and Medlar leaf extracts against ESBLs harboring ESBL isolates, well diffusion method and broth macro dilution method was used to determine the minimum inhibitory concentration and minimum bactericidal concentration. Results: 26 Out of 45 isolates, 57% phenotypically recognized as ESBL producing and based on the results of PCR, the prevalence of SHV genes among ESBLs-positive isolates was 42% SHV and 11% TEM positive isolates were detected. MIC of Eucalyptus extracts ranged between 17/5 - 31mg/ml and Medlar extracts ranged between 165-250 mg/ml. MBC of Eucalyptus extracts ranged between 600-1000mg/ml and Medlar extracts 500-1000mg/ml. Conclusion: The obtained results showed that Eucalyptus and Medlar extracts possess significant antibacterial activity against resistant bacteria. So these plant extracts may be used as an accomplishment in Klebsiella infection treatment, particularly in topical treatment of urinary tract infections.